2019
DOI: 10.1523/jneurosci.2942-18.2019
|View full text |Cite
|
Sign up to set email alerts
|

PMP22 Regulates Cholesterol Trafficking and ABCA1-Mediated Cholesterol Efflux

Abstract: The absence of functional peripheral myelin protein 22 (PMP22) is associated with shortened lifespan in rodents and severe peripheral nerve myelin abnormalities in several species including humans. Schwann cells and nerves from PMP22 knock-out (KO) mice show deranged cholesterol distribution and aberrant lipid raft morphology, supporting an unrecognized role for PMP22 in cellular lipid metabolism. To examine the mechanisms underlying these abnormalities, we studied Schwann cells and nerves from male and female… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 96 publications
1
38
0
Order By: Relevance
“…We next tested whether either or both of the predicted cholesterol binding sites in PMP22 play a role in its ordered phase preference. It has been shown that pmp22 -/-Schwann cells exhibit reduced plasma membrane levels and abnormal localization of cholesterol (30,32). These cells also show reduced migration, adhesion, and lamellipodia extension, all of which can be restored through external supplementation of cholesterol in the culture media.…”
Section: Cholesterol Binding Motifs In Pmp22 Do Not Mediate Its Ordermentioning
confidence: 99%
See 2 more Smart Citations
“…We next tested whether either or both of the predicted cholesterol binding sites in PMP22 play a role in its ordered phase preference. It has been shown that pmp22 -/-Schwann cells exhibit reduced plasma membrane levels and abnormal localization of cholesterol (30,32). These cells also show reduced migration, adhesion, and lamellipodia extension, all of which can be restored through external supplementation of cholesterol in the culture media.…”
Section: Cholesterol Binding Motifs In Pmp22 Do Not Mediate Its Ordermentioning
confidence: 99%
“…5C). This may be due to an increased concentration in cholesterol in PMP22-containing GPMVs since it has recently been shown that PMP22 is regulates cholesterol PM trafficking (32). It seems likely that the mechanisms underpinning this regulatory function of PMP22, as well as its ability to promote ordered phase formation, is closely related to its preference to partition into ordered membrane phase domains.…”
Section: Pmp22-containing Gpmvs Exhibited a Higher T Misc Than Gpmvs mentioning
confidence: 99%
See 1 more Smart Citation
“…Images were acquired on a Nikon A1RMPsi laser‐scanning confocal microscope and were analyzed using Nikon NIS Elements Software 4.40 or 4.51 (Zhou, Miles, et al, 2019). Background‐reduced images after 2D deconvolution were quantified for subcellular filipin intensity.…”
Section: Methodsmentioning
confidence: 99%
“…However, in CMT1A rats, which overexpress PMP22, genes related to sterol metabolism are significantly downregulated (Fledrich et al, 2018), while nerves from Trembler (Tr) mice carrying a glycine (G) 150 to aspartic acid (D) mutation in PMP22 exhibited reduced cholesterol levels and synthesis (Bourre, Morand, Dumont, Boutry, & Hauw, 1981; Clouet & Bourre, 1988; Heape, Juguelin, Fabre, Boiron, & Cassagne, 1986; Yao & Bourre, 1985). Recently, through the study of cells and tissue from PMP22 knockout (KO) mice, we discovered the requirement for PMP22 in cholesterol efflux from Schwann cells (Zhou, Miles, et al, 2019).…”
Section: Introductionmentioning
confidence: 99%